Genetic polymorphisms in folate pathway enzymes, DRD4 and GSTM1 are related to temporomandibular disorder - Mayor-Olea Alvaro; Aguado Lidia; Perez-Nevot Beatriz; Palomares Arturo R; Lendinez Ana M; Aneiros-Guerrero Angel; Ruiz-Galdon Maximiliano; Reyes-Engel Armando (BMC, 2011)
Abstract Background Temporomandibular disorder (TMD) is a multifactorial syndrome related to a critical period of human life. TMD has been associated with psychological dysfunctions, oxidative state and sexual dimorphism with coincidental occurrence along the pubertal development. In this work we study the association between TMD and genetic polymorphisms of folate metabolism, neurotransmission, oxidative and hormonal metabolism. Folate metabolism, which depends on genes variations and diet, is directly involved in genetic and epigenetic variations that can influence the changes of last growing period of development in human and the appearance of the TMD. Methods A case-control study was designed to evaluate the impact of genetic polymorphisms above described on TMD. A total of 229 individuals (69% women) were included at the study; 86 were patients with TMD and 143 were healthy control subjects. Subjects underwent to a clinical examination following the guidelines by the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Genotyping of 20 Single Nucleotide Polymorphisms (SNPs), divided in two groups, was performed by multiplex minisequencing preceded by multiplex PCR. Other seven genetic polymorphisms different from SNPs (deletions, insertions, tandem repeat, null genotype) were achieved by a multiplex-PCR. A chi-square test was performed to determine the differences in genotype and allelic frequencies between TMD patients and healthy subjects. To estimate TMD risk, in those polymorphisms that shown significant differences, odds ratio (OR) with a 95% of confidence interval were calculated. Results Six of the polymorphisms showed statistical associations with TMD. Four of them are related to enzymes of folates metabolism: Allele G of Serine Hydoxymethyltransferase 1 (SHMT1) rs1979277 (OR = 3.99; 95%CI 1.72, 9.25; p = 0.002), allele G of SHMT1 rs638416 (OR = 2.80; 95%CI 1.51, 5.21; p = 0.013), allele T of Methylentetrahydrofolate Dehydrogenase (MTHFD) rs2236225 (OR = 3.09; 95%CI 1.27, 7.50; p = 0.016) and allele A of Methionine Synthase Reductase (MTRR) rs1801394 (OR = 2.35; 95CI 1.10, 5.00; p = 0.037). An inflammatory oxidative stress enzyme, Gluthatione S-Tranferase Mu-1(GSTM1), null allele (OR = 2.21; 95%CI 1.24, 4.36; p = 0.030) and a neurotransmission receptor, Dopamine Receptor D4 (DRD4), long allele of 48 bp-repeat (OR = 3.62; 95%CI 0.76, 17.26; p = 0.161). Conclusions Some genetic polymorphisms related to folates metabolism, inflammatory oxidative stress, and neurotransmission responses to pain, has been significantly associated to TMD syndrome